SOME STUDENTS'ATTITUDES TOWARDS PHYSICAL EDUCATION - Rabit Veseli; Arianit Morina; Musa Selimi; Nazim Myrtaj; Afrim Selimi (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The subject of physical education (kinesiology) at primary schools in Kosovo is present in school programs with three classes weekly. In order to form a realistic idea of what students feel about their teacher in Physical Education as well as of the implementation of the educational program, we conducted a questionnaire survey. Methods: The survey examines 210 respondents (118 school boys and 92 school girls) at the age of 14. It was conducted mainly to establish and compare the attitudes of boys and girls on the base of their answers to the following six questions: 1. Is the teacher in Physical Education always dressed in sports equipment in class? 2. Is the teacher always present and active in class performances? 3. Does the teacher form realistic marks to your performance? 4. Does the school possess the necessary facilities and equipment for the realization of the class program? 5. Do you regularly wear sports equipment in your Physical Education classes? 6. Are you happy with the way your PhE classes are conducted? Results & Discussion: According to the answers to each question the groups of boys and girls are considered individually through methods of frequency and percentage of results. The differences between boys' and girls' attitudes are tested by non-parametric chi-square test, at the level of 0,05(5%). According to the fi nal results, the conclusion is that school boys and girls have similar attitudes (do not differ) in their answers to questions 5 and 6. To some extent, the results obtained from the survey show similarity with the research conducted by Memedi, Nika and Hajredini (2011).